Mechanical properties and anatomical characteristics of Oecopetalum mexicanum Greenm. & C.H. Thomps. (Icacinaceae) wood of the la sierra de Misantla, Veracruz, Mexico - Lascurain, Maite; Angeles-Álvarez, Guillermo; Ortega Escalona, Fernando; Ordóñez Candelaria, Víctor Rubén; Ambrosio, Mirna; Avendaño, Sergio (Instituto de Ecología, A.C., 2016)
The wood anatomy of Oecopetalum mexicanum Greenm. & C. H. Thomps. is described for the first time. This species grows in the forest and coffee ecosystem of the sierra de Misantla, Veracruz, Mexico. In order to recommend possible uses, mechanical properties essays of different types were carried out. These were: bending, like stress at proportional limit, unit work to proportional limit, modulus of elasticity, modulus of rupture, and unit work to maximum load in bending; parallel compression to grain, like maximum strength, stress at proportional limit and modulus of elasticity. All these essays were performed in green wood condition. For each sample, specific gravity was obtained. Vessel diameter, density and distribution, and estimation of abundance and distribution of axial and radial parenchyma were measured from permanent slides. Fiber and vessel elements length, as well as cell contents, were determined from macerated wood samples. Anatomical descriptions were made according to the IAWA List of microscopic features for hardwood identification ( IAWA 1989). The results so far obtained suggest that el cachichín wood is as resistant as pine wood and, for some mechanical properties, this is better than pine wood. Therefore, it is apt as building material, provided the whole bole is used; only if dimensions allowed, it could be saw for making prismatic pieces.